Efektifitas Metode Pelaksanaan Erection Struktur Baja Menggunakan Alat Bantu Box I Studi Kasus Proyek Pembangunan Lapangan Petanque Unesa - Al Ghozy, Mochamad Yusuf; S, Suprapto (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The Unesa Petanque Field Development Project is an effort to improve sports facilities that support academic and non-academic activities. A pivotal element of this endeavor lies in the fabrication of steel frameworks, which necessitates a tailored approach due to spatial constraints and restricted machinery accessibility. This study aims to assess the implementation of the Box I technique in the assembly of steel frames, emphasizing its adaptability to on-site challenges, procedural execution, and installation integrity. The Box I method was chosen for its capacity to navigate space limitations and access difficulties while ensuring workplace safety. Employing a qualitative methodology, the research gathers insights through observation, interviews, and documentation. The results indicate that the Box I technique proficiently mitigates site-specific obstacles, optimizes operational efficiency, and guarantees precise and secure installation. Recommendations are made for the formulation of Standard Operating Procedures (SOPs) applicable to similar undertakings.